Recent drying of the Ganga River is unprecedented in the last 1,300 years - Dipesh Singh Chuphal; Kaustubh Thirumalai; Vimal Mishra (Proceedings of the National Academy of Sciences, 2025)
The Ganga River basin, critical to over 600 million people, is experiencing a severe and unprecedented drying trend, threatening water and food security. Using streamflow reconstructions spanning 1,300 y (700–2012 C.E.) from instrumental data, paleohydrological records, and hydrological modeling, we show that drying from 1991 to 2020 is unmatched in the past millennium. Streamflow decline since the 1990s, driven by frequent and prolonged droughts, is 76% more intense than the 16th-century drought—the closest historical analogue. This drying exceeds natural variability, highlighting the dominant role of anthropogenic factors. Despite CMIP6 models projecting increased streamflow under warming scenarios, the recent decline indicates complexities associated with future water availability projections. Our findings underscore the urgent need to examine the interactions among the factors that control summer monsoon precipitation, including large−scale climate variability and anthropogenic forcings. Better constraints on these processes in climate models will be essential for improving future monsoon projections and implementing adaptive water management strategies to secure the Ganga basin’s freshwater availability under a changing climate.